A Model for Active Transport of Sodium and Potassium Ions as Mediated by a Tetrameric Enzyme - Stein, W. D. (1973)
A new model is proposed for the system that actively transports sodium and potassium ions across animal-cell membranes. The model is based on the physical and chemical properties of transport-associated adenosine triphosphatase (EC 3.6.1.3) and on the kinetics of ion movements mediated by the system. Transport is postulated to occur by internal transfer of cations across a protein tetramer embedded in the cell membrane. The protein tetramer can exist in either of two forms of identical energy; transport occurs as a result of the sequential “flipping” from one conformation to the other. The conformation change results in the interchanging of the affinities of cation-binding sites associated with different sub-units of the tetramer, with a concomitant splitting of adenosine triphosphate.